2016
DOI: 10.1002/kin.21062
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Reaction Mechanism and Kinetics of HO2 with XCHO (X = F, Cl)

Abstract: The reactions of HO 2 with FCHO and ClCHO have been theoretically investigated by combining beyond-CCSD(T) electronic structure benchmarks, validated density functional theory, and canonical variational transition state theory with small-curvature tunneling, coupledtorsions anharmonicity, and high-frequency anharmonicity. This investigation explores three different reaction mechanisms: radical addition plus a hydrogen transfer, radical addition, and hydrogen abstraction. The calculated results show that the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…We have obtained the benchmark barrier heights of hydrogen atom transfer reactions for CH 3 O to CH 2 OH by different catalysts at the W3X-L//CCSD(T)-F12a/VDZ-F12 level as our best estimate. It is worth noting that W3X-L composite methods have been used in the reactions of Criegee intermediates with water, 25 SO 2 with OH, 43 and HO 2 with XCHO 44 to obtain rate constants with experimental accuracy.…”
Section: Benchmark Calculationmentioning
confidence: 99%
“…We have obtained the benchmark barrier heights of hydrogen atom transfer reactions for CH 3 O to CH 2 OH by different catalysts at the W3X-L//CCSD(T)-F12a/VDZ-F12 level as our best estimate. It is worth noting that W3X-L composite methods have been used in the reactions of Criegee intermediates with water, 25 SO 2 with OH, 43 and HO 2 with XCHO 44 to obtain rate constants with experimental accuracy.…”
Section: Benchmark Calculationmentioning
confidence: 99%
“…36,37 The rate constant of the HFCO + NO 3 reaction is 2.09 × 10 –23 cm 3 molecule –1 s –1 , 37 and the corresponding atmospheric lifetime of HFCO is about 1.52 × 10 5 years at 298 K when nighttime NO 3 concentration is 1 × 10 10 molecule cm –3 . 38 Additionally, the rate constant of the HFCO + HO 2 reaction is 2.19 × 10 –18 cm 3 molecule –1 s –1 at 298 K 39 and the corresponding atmospheric lifetime of HFCO is expected to be ∼13 years when the concentration of HO 2 is 1.1 × 10 9 molecule cm –3 . 39 The previous results have shown that the HFCO + OH reaction dominates the sink of HFCO.…”
Section: Introductionmentioning
confidence: 99%
“…38 Additionally, the rate constant of the HFCO + HO 2 reaction is 2.19 × 10 −18 cm 3 molecule −1 s −1 at 298 K 39 and the corresponding atmospheric lifetime of HFCO is expected to be ∼13 years when the concentration of HO 2 is 1.1 × 10 9 molecule cm −3 . 39 The previous results have shown that the HFCO + OH reaction dominates the sink of HFCO. However, the reaction of HFCO with OH is still quite slow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent reaction pathway of HO 2 would affect the composition of the troposphere. Therefore, reactions involving HO 2 have been extensively studied with HX (X = F, Cl, Br, I), 12 H 2 CO, 13 XCHO (X = F, Cl), 14 and HCNO. 15 However, to our best knowledge, the reaction of HO 2 and HNCO has never been reported.…”
Section: Introductionmentioning
confidence: 99%